(2+3) amide cages by oxidation of (2+3) imine cages: revisiting molecular hosts for highly efficient nitrate binding - Lauer, Jochen; Bhat, Avinash S.; Barwig, Chantal; Fritz, Nathalie; Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2022)
The pollution of groundwater with nitrate is a serious issue because nitrate can cause several diseases such as methemoglobinemia or cancer. Therefore, selective removal of nitrate by efficient binding to supramolecular hosts is highly desired. Here we describe how to make [2+3] amide cages in very high to quantitative yields by applying an optimized Pinnick oxidation protocol for the conversion of corresponding imine cages. By NMR titration experiments of the eight different [2+3] amide cages with nitrate, chloride and hydrogen sulfate we identified one cage with an unprecedented high selectivity towards nitrate binding vs. chloride (S=705) or hydrogensulfate (S>13500) in CD2Cl2/CD3CN (1 : 3). NMR experiments as well as single-crystal structure comparison of host-guest complexes give insight into structure-property-relationships.